Fungal network responses to grazing. - Boddy, L; Wood, J; Redman, E; Hynes, J; Fricker, M (2010)
Mycelial networks operate on scales from microscopic to many m(2) and naturally persist for extended periods. As fungi exhibit highly adaptive development, it is important to test behavioural responses on natural substrata with realistic nutrient levels across a range of spatial scales and extended time periods. Here we quantified network responses over 7.5 months in large (57 x 57cm) microcosms to test whether grazing shifts the network to a more resilient architecture. Resource limitation constrained any ability to respond at all, with both grazed and ungrazed networks gradually thinning out over time. Added resources sustained further exploratory growth, but only transiently increased cross-connectivity and network resilience, when tested by simulated damage in silico. Grazed networks were initially weaker and emergence of new exploratory growth was curtailed. However, increased interstitial proliferation led to new cross-links, consolidating the existing mycelial network and increasing the resilience of the network to further attack.